Transforming Technology: A Critical Theory Revisited - Feenberg, Andrew (Oxford University Press, 2002)
Thoroughly revised, this new edition of Critical Theory of Technology rethinks the relationships between technology, rationality, and democracy, arguing that the degradation of labor--as well as of many environmental, educational, and political systems--is rooted in the social values that preside over technological development. It contains materials on political theory, but the emphasis has shifted to reflect a growing interest in the fields of technology and cultural studies.
Keywords: Political Science / History & Theory; Political Science / Public Policy / Social Services & Welfare